Cerebral blood flow links insulin resistance and baroreflex sensitivity. - John P Ryan; Lei K Sheu; Timothy D Verstynen; Ikechukwu C Onyewuenyi; Peter J Gianaros (PLoS ONE)
Insulin resistance confers risk for diabetes mellitus and associates with a reduced capacity of the arterial baroreflex to regulate blood pressure. Importantly, several brain regions that comprise the central autonomic network, which controls the baroreflex, are also sensitive to the neuromodulatory effects of insulin. However, it is unknown whether peripheral insulin resistance relates to activity within central autonomic network regions, which may in turn relate to reduced baroreflex regulation. Accordingly, we tested whether resting cerebral blood flow within central autonomic regions statistically mediated the relationship between insulin resistance and an indirect indicator of baroreflex regulation; namely, baroreflex sensitivity. Subjects were 92 community-dwelling adults free of confounding medical illnesses (48 men, 30-50 years old) who completed protocols to assess fasting insulin and glucose levels, resting baroreflex sensitivity, and resting cerebral blood flow. Baroreflex sensitivity was quantified by measuring the magnitude of spontaneous and sequential associations between beat-by-beat systolic blood pressure and heart rate changes. Individuals with greater insulin resistance, as measured by the homeostatic model assessment, exhibited reduced baroreflex sensitivity (b = -0.16, p < .05). Moreover, the relationship between insulin resistance and baroreflex sensitivity was statistically mediated by cerebral blood flow in central autonomic regions, including the insula and cingulate cortex (mediation coefficients < -0.06, p-values < .01). Activity within the central autonomic network may link insulin resistance to reduced baroreflex sensitivity. Our observations may help to characterize the neural pathways by which insulin resistance, and possibly diabetes mellitus, relates to adverse cardiovascular outcomes.